2021
DOI: 10.1002/ardp.202100029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of new coumarin derivatives as cytotoxic agents

Abstract: New coumarin derivatives 9a–f, 10a–e, and 11a–f were synthesized and evaluated for their cytotoxic activity against a human breast cancer cell line (MCF‐7). All compounds exhibited good activity in the nanomolar range, using doxorubicin and erlotinib as positive controls. The most active compound 9d with IC50 of 21 nM was tested against the HCT‐116, HepG‐2, A549, and SGC‐7901 cell lines, with IC50 values of 0.021, 0.170, 0.028, and 0.11 µM, respectively. Compound 9d was further investigated for its ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Erlotinib (IC 50 = 2 n m ) and icotinib (IC 50 = 5 n m ) are potent and selective EGFR inhibitors approved to treat non‐small cell lung cancer (NSCLC) 32–34 . In addition, erlotinib has been used as a positive control in several studies of EGFR inhibition 35–37 . Besides, Almalki Faisal et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Erlotinib (IC 50 = 2 n m ) and icotinib (IC 50 = 5 n m ) are potent and selective EGFR inhibitors approved to treat non‐small cell lung cancer (NSCLC) 32–34 . In addition, erlotinib has been used as a positive control in several studies of EGFR inhibition 35–37 . Besides, Almalki Faisal et al.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] In addition, erlotinib has been used as a positive control in several studies of EGFR inhibition. [35][36][37] Besides, Almalki Faisal et al found that icotinib exhibited a binding energy of −8.42 kcal/mol compared with −7.26 kcal/mol for erlotinib, predicting that high binding affinity corresponds to the strong inhibitory effect on EGFR. 17 Also in this study, the authors demonstrated that both icotinib and erlotinib have similar hydrophobic interactions with hydrophobic moieties in EGFR, a finding that is consistent with our study.…”
Section: Molecular Docking Of Compounds To the Target Proteinmentioning
confidence: 99%
“…Some of the compounds of coumarine and pyrazole were acting by inhibiting epidermal growth factor receptor [6b,33–35] . Accordingly, the five potent compounds 5 d , 5 e , 5 i , 5 j and 5 o were screened to know binding affinity towards epidermal growth factor receptor (EGFR) and the results were presented as table S1, in ESI.…”
Section: Resultsmentioning
confidence: 99%